Router jigs and techniques with Bernie Maas and Michael Fortune. - Fortune, Michael; Maas, Bernie (Newtown, CT : Taunton Press, 1986)
Mass covers basic router joinery, including: spline joint; mortise-and-tenon; and the sliding dovetail. Fortune demonstrates a series of jigs to produce a hand-mirror project
DVD
Keywords: Cabinetwork; Joinery; Routers (Tools).